Mengoptimalkan Pembelajaran Pendidikan Agama Buddha Melalui Learning Analytics - Sukodoyo Sukodoyo; Tri Saputra Medhacitto; Parsiyono Parsiyono (Institut Nalanda, 2025)
This research examines the integration of learning analytics in Buddhist education using a literature review approach. The study is conducted through a conceptual synthesis framework consisting of three stages: preliminary synthesis, intermediate synthesis, and final synthesis. The primary focus of the research is how learning analytics, as a data-driven technological tool, can be utilized to support personalized and meaningful learning processes, without neglecting the core values of Buddhist teachings. In this context, learning analytics is positioned not merely as a technical instrument, but as a reflective medium capable of incorporating the principles of sīla (ethics), samādhi (concentration), and prajñā (wisdom) into students' learning experiences. The analysis is conducted by considering three main elements: text, which encompasses the content of Buddhist teachings and student learning data; context, namely the dynamics of digital transformation in the spiritual education system; and discourse, namely the reinterpretation of Buddhist learning that is holistic, contemplative, and relevant to the needs of the times. The study's findings demonstrate that integrating learning analytics into Buddhist education enables the creation of a learning process that is not only adaptive and evidence-based, but also deeply spiritual and ethical. When implemented appropriately, learning analytics has the potential to support inclusive, mindfulness-based, and sustainable education—where technology is used not to replace spiritual values, but to enhance them. This study provides a conceptual contribution to the development of a digital pedagogical model that balances technological sophistication with spiritual depth, and encourages the wise and ethical use of data in religious education. These findings can provide a starting point for curriculum designers, educators, and educational technology developers in designing Buddhist learning approaches relevant to the digital age.